Radiosynthesis and evaluation of a 99mTc-folic acid radiotracer prepared using [99mTcN(PNP)]2+ metal fragment. Issue 5 (1st March 2017) - Vats, Kusum; Subramanian, Suresh; Mathur, Anupam; Sarma, Haladhar Dev; Banerjee, Sharmila
Graphical abstract: Abstract: Folate receptors (FR) are over-expressed on a wide variety of tumor cells and are a potential molecular target for radiolabeled folates. In this respect, several SPECT and PET based radiofolates have been evaluated in the past albeit with their high renal uptake posing limitation towards their clinical use. To overcome this, a new 99m Tc labeled folic acid was synthesized via the use of [ 99m TcN(PNP)] 2+ metal fragment, where the presence of the latter pharmacophore redirects in vivo clearance via the hepatobiliary pathway. In this respect, folic acid was derivatized at the γ-acid group with a cysteine BFCA (bifunctional chelating agent) and subsequently reacted with the preformed [ 99m TcN] 2+ intermediate in presence of PNP2 (bisphosphine) ligand, to yield the final complex. While preliminary, in vivo distribution of the complex exhibited high association of activity with liver and intestines and provided support to the rationality of the present design as clearance of labeled folic acid could be effected via the hepatic route, the in vitro studies of the folic acid-cysteine conjugate carried out in KB-31 cells, did not show much promise with reduction in receptor affinity in comparison with the native folic acid. The route followed herein to prepare a folic-acid based radiotracer constitutes the first report of radiolabeling folic acid using the [ 99m TcN(PNP)] 2+ as a radiosynthon. Modification in the structure of conjugate by linking the BFCA through a long-chain linker can be envisaged to improve the affinity of [ 99m TcN(PNP)]-folic acid complex towards FRs.